Metodología para optimizar la capacidad de centros de distribución con base en el modelo de transporte (2014)
This article presents a methodology to improve the economic performance of the transport model, overcoming previous optimization methods, based on the sensitivity analysis that generates Excel Solver. The methodology is directed to modify the capacity of distribution centers taking as reference the shadow price.